Association of polymorphisms in 5-HTT (SLC6A4) and MAOA genes with measures of obesity in young adults of Portuguese origin. (1st January 2016) - Dias, Helena; Muc, Magdalena; Padez, Cristina; Manco, Licínio
Abstract: Objectives : To investigate the association of polymorphisms in SLC6A4 and MAOA genes with overweight (including obesity). Material and methods : Young adults ( n = 535) of Portuguese origin were genotyped for the SLC6A4 polymorphisms 5-HTTLPR and STin2 and a MAOA VNTR. BMI and body fat percentage were measured and a questionnaire was used to assess individual's sport practicing habits. Results : In whole study sample, haplotype-based analysis revealed significant association with overweight/obesity for the individual 5-HTTLPR/Stin2 haplotype L10 ( p = 0.04). In men, the MAOA 3R genotype was nominally associated with body fat ( p = 0.04). In inactive individuals, overweight/obesity was found significantly associated with 5-HTTLPR L-allele ( p = 0.01) and nominally associated with STin2 10-allele ( p = 0.03). A significant association was also found testing for all haplotype effects ( χ 2 = 8.7; p = 0.03). Conclusions : We found some evidences for the association of SLC6A4 and MAOA genes with measures of obesity. Our results suggest physical inactivity accentuates the influence of SLC6A4 polymorphisms on obesity risk.